Effectiveness Back in the back and Round Robin Strategies In Developing the Skills Listening In the Subject of expression for the second intermediate female students (Journal of the College of Basic Education, 2022)
The current research aims to know: " Effectiveness Back in the back and Round Robin Strategies In Developing the Skills Listening In the Subject of expression for the second intermediate female students " in the light of the goal of the search researcher developed the following assumptions:1- there is no difference statistically significant level (0.05) between the Mediterranean degrees conference the first pilot group in listening skills to the use of the Back in the back strategy. 2- There is no difference d statistically significant level (0.05) between the Mediterranean degrees conference in the second experimental group in listening skills to the use of the Round Robin strategy.3- There is no difference d statistically significant level (0.05) between the AVERAGES of the degrees of the three groups in the a posteriori tests in listening skills.4- there is no effective Back in the back Strategies In Developing the Skills of Dialogue Listening.5- there is no effective Round Robin Strategies In Developing the Skills of Dialogue Listening. And To achieve the research goal and hypotheses, researcher followed the procedures of the experimental approach, and chose experimental design based on the test Conference incorporated MICS modules into three, one of them is control and the other two are experimental is one of the experimental designs of partial reset, As for the research sample the researcher intentionally chose a middle school for girls of the Directorate General for the breeding of Baghdad Governorate Rasafa al/education the eastern outskirts of Baghdad, for the academic year (2018 - 2019m), It is a medium Shaima for girls located in the kemalism, As the number of female students of the research sample (115) Student divided in to three groups, then she rewarded the researcher between the three research groups, the researcher studied the research groups themselves during the second semester, the researcher also prepared tool and applied them to the three groups, it was a pre-and post-test of listening skills.The result showed the superiority of the students of the two experimental groups, who studied according to the Strategies of the Back in the back and Round Robin, students of the control group who studied according to the traditional method.